Rendimiento agronómico del cultivo de orégano (Origanum vulgare L.), mediante la fertilización orgánica con tres tipos de bioles, en el cantón Montufar, provincia del Carchi - Carlosama Bastidas, Fredy Esteban (2017)
VIII SUMMARY. The research was conducted with the purpose of the study of the application of three bioles and three doses performance oregano (Origanum vulgare L.), such research is conducted in the community Canchaguano, Canton Montufar, Carchi province, located in the geographical coordinates 00 ° 32' 39,6'' north latitude and 77 ° 48' 40'', west longitude at an altitude of 2,852 meters above sea level, with the aim of obtaining data results applications with high doses bioles , medium and low, looking for the most appropriate treatment for better economic performance. The research was made in ten treatments by combining three applications bioles and three doses and a witness, using an experimental design complete block design at random (DBCA) with a factorial arrangement A x B + 1, with 10 treatments and 3 repetitions, giving a total of 30 experimental units in a total area of 656 m2, with experimental plots of 12,00 m2 and a total net area of 5.12 m2. efficiency with the bioles and dose rate of engraftment, plant height, stem diameter, yield of green and dry oregano matter, and an economic analysis of each treatment, checking treatment means determined it was performed by the multiple range test of Duncan at 5% probability. The results obtained showed that the cultivation of oregano responded favorably to the application of bioles and dose generating the highest percentage of engraftment, high silver, stem diameter, yield of green matter and dry, which obtained the best net profit, compared to the control without application. That investigation cleared doubts regarding the most appropriate biological and dose that best performance, quality and generate net profit to the farmer, concluding that the cultivation without application does not generate any statistically compared.